2012
DOI: 10.2139/ssrn.2179781
|View full text |Cite
|
Sign up to set email alerts
|

General Equilibrium and the New Neoclassical Synthesis

Abstract: We present a general equilibrium model of the new neoclassical synthesis that has the same level of generality as the Arrow-Debreu model. This involves a stochastic multiperiod economy with a monetary sector and sticky commodity prices. We formulate the notion of a sticky price equilibrium where all agents form rational expectations on prices for commodities and assets, interest rates, and rationing. We present a general result showing that monetary policy imposes no restrictions whatsoever on nominal equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…A very important implication of nominal wage/price rigidities is the existence of multiple equilibria. This has been demonstrated for the GEI model in a number of papers, including for instance Citanna et al (2001), Drèze (1997) or Herings (2012). Drèze (2013b) extends the main result to the more realistic Temporary General Equilibrium (TGE) model.…”
Section: Microeconomic Implications Of Market Incompletenesssupporting
confidence: 53%
“…A very important implication of nominal wage/price rigidities is the existence of multiple equilibria. This has been demonstrated for the GEI model in a number of papers, including for instance Citanna et al (2001), Drèze (1997) or Herings (2012). Drèze (2013b) extends the main result to the more realistic Temporary General Equilibrium (TGE) model.…”
Section: Microeconomic Implications Of Market Incompletenesssupporting
confidence: 53%
“…Van der Laan (1980), Kurz (1982), Dehez and Drèze (1984), Drèze (1997), and Citanna et al (2001) are all related Drèze (1975)'s original work, and study the properties of supply-constrained economy and explore the connection between price distortion and coordination failure. Herings (1996Herings ( , 2014 extend Drèze (1975)'s work to settings with more flexible primitives and to dynamic environments. Bénassy (1993) compares the original Drèze equilibrium with other closely related disequilibrium concepts, and explore their implications in a static monetary economy with fixed prices and a fixed wage.…”
Section: Related Literaturementioning
confidence: 89%
“…The modelling of nominal rigidities equilibria follows the fix-price literature. Notable contributions, among others, include: Barro and Grossman (1971), Benassy (1975), Dreze (1975), Malinvaud (1977), Laroque (1978), Silvestre (1982) and Herings (2014). Money is modelled as an argument of the utility function as in the static frameworks of Malinvaud (1977) and Laroque (1978) or as a store of value, and an argument of the indirect utility function, that links periods as in Benassy (1975).…”
Section: Literaturementioning
confidence: 99%
“…Silvestre (1980) and Citanna et al (2001), in environments without policy, demonstrated existence of equilibria with Keynesian features as a result of coordination failures. Herings (2014) characterised sticky-price equilibria in an economy with a transaction technology for money that incorporates cash-in-advance as a special case, monetary policy sets the nominal interest rate and importantly, fiscal policy is Ricardian.…”
Section: Literaturementioning
confidence: 99%